Novel M4 positive allosteric modulators derived from questioning the role and impact of a presumed intramolecular hydrogen-bonding motif in β-amino carboxamide-harboring ligands. Issue 3 (1st February 2019) - Poslusney, Michael S.; Salovich, James M.; Wood, Michael R.; Melancon, Bruce J.; Bollinger, Katrina A.; Luscombe, Vincent B.; Rodriguez, Alice L.; Engers, Darren W.; Bridges, Thomas M.; Niswender, Colleen M.; Conn, P. Jeffrey; Lindsley, Craig W.
Graphical abstract: Highlights: First description of the role of the β-aminocarboxamide moiety within M4 PAM scaffolds. Novel des -amino and tricyclic variant M4 PAMs. The role of the IMHB motif was established, and could be re-enforced by tricycles. Abstract: This letter describes a focused exercise to explore the role of the β-amino carboxamide moiety found in all of the first generation M4 PAMs and question if the NH2 group served solely to stabilize an intramolecular hydrogen bond (IMHB) and enforce planarity. To address this issue (and to potentially find a substitute for the β-amino carboxamide that engendered P-gp and contributed to solubility liabilities), we removed the NH2, generating des -amino congeners and surveyed other functional groups in the β-position. These modifications led to weak M4 PAMs with poor DMPK properties. Cyclization of the β-amino carboxamide moiety by virtue of a pyrazole ring re-enforced the IMHB, led to potent (and patented) M4 PAMs, many as potent as the classical bicyclic β-amino carboxamide analogs, but with significant CYP1A2 inhibition. Overall, this exercise indicated that the β-amino carboxamide moiety most likely facilitates an IMHB, and is essential for M4 PAM activity within classical bicyclic M4 PAM scaffolds.